Total Failure of Fenbendazole to Control Strongylid Infections in Czech Horse Operations - Nápravníková, Jana; Várady, Marián; Vadlejch, Jaroslav (Frontiers in Veterinary Science, 2022)
The control of strongylid infections has become challenging globally for equine practitioners due to the development of anthelmintic resistance. Comprehensive information on anthelmintic resistance in the Czech Republic, however, is still lacking. This study monitored the current efficacy of fenbendazole, pyrantel embonate, ivermectin and moxidectin. Forty-eight of 71 operations met the criteria (≥6 horses with ≥200 eggs per gram), with 969 fecal egg count reduction tests performed. Anthelmintic resistance was evaluated on an operation level based on fecal egg count reduction (FECR) and the lower limit of the 95% credible interval (LLCI) using Bayesian hierarchical models. General anthelmintic efficacy across all operations was assessed by posterior FECRs and the occurrence of sub-zero efficacies. Ivermectin and moxidectin demonstrated excellent efficacy (FECR 99.8–100%; 99.4–100 LLCI) in 45 and 23 operations, respectively, pyrantel embonate demonstrated sufficient efficacy in 15 operations and resistance was suspected in seven operations (FECR 88.1–99.1%; 72.5–98.5 LLCI). Fenbendazole, however, was not effective in a single operation (FECR 19.1–77.8%; 8.1–50.1 LLCI) out of 18. Fenbendazole had the highest probability of sub-zero efficacy (29.1%), i.e. post-treatment fecal egg counts exceeded the pre-treatment counts. Our data indicate an increase in the development of anthelmintic resistance, resulting in total failure of fenbendazole and a reduced efficacy of pyrantel embonate. Introducing advanced approaches of parasite control in the Czech Republic to slow the spread of anthelmintic resistance is thus needed.